Gwarancje prawa do nauki w projektach konstytucji - Skotnicki, Krzysztof (Wydział Prawa i Administracji UAM, 1995)
Analysing several drafts of the new Constitution of the Republic of Poland the author has noticed a very limited range of legal regulations ensuring the right to learn. The proposed drafts do not - in the author/s opinion guarantee that rigth in the same scope as the Constitution of 1921 did.
Guarantees of the right to learn in the drafts of new Constitution